Assessing Accommodation Suppliers’ Perceptions of Climate Change Adaptation Actions on Koh Phi Phi Island, Thailand - Janto S. Hess; Rachel Dodds; Ilan Kelman (ASEAN Journal on Hospitality and Tourism, 2021)
Koh Phi Phi Don is among the most visited island tourism destinations in Thailand. Due to the island’s topography and development patterns, most accommodation suppliers on the island are likely to be exposed to a range of climate change impacts, particularly sea-level rise, which can pose a severe risk to the local tourism operations. This study aimed to explore perceptions of climate change adaptation actions in response to impacts typically associated with climate change. This study, furthermore, investigated possible obstacles, barriers, and incentives influencing decision-making processes of accommodation owner-managers (the private sector) to adapt to climate change. The investigation builds on 81 surveys and 12 in-depth interviews. The findings provide evidence that most of the sampled businesses already implemented (consciously or not) climate change adaptation measures, such as insurance coverage, water treatment appliances, and staff training on emergency responses. Through a concentration of power on the island, their action is hindered, which creates a barrier to a sustainable and climate risk-informed development pathway.